Nonsurgical Treatment of Chest Wall Deformities: Contradiction or Complement? - Häcker, Frank-Martin (European Journal of Pediatric Surgery, 2018)
For decades, open surgical repair was the only available method to treat congenital and acquired chest wall deformities (CWDs). In 1998, D. Nuss described a minimally invasive procedure for surgical repair of pectus excavatum (PE), and a few years later H. Abramson reported on his experience with the “reversed Nuss technique” for surgical repair of pectus carinatum (PC). Both procedures are performed with increasing frequency worldwide.However, nonsurgical measures such as vacuum bell (VB) therapy for conservative treatment of PE and more differentiated bracing systems for conservative treatment of PC were established 15 to 20 years ago. Nowadays, information on new therapeutic modalities circulates not only among surgeons and pediatricians, but also rapidly among patients. In particular, patients who refused operative treatment by previously available procedures now appear at the outpatient clinic and request to be considered for the new methods.Analyzing the increasing number of studies reporting on conservative treatment of CWDs as well as our own group of patients who visited a busy outpatient clinic in a small country within the last 15 to 20 years, we have to realize that the majority of patients asked for nonsurgical treatment of their CWD. Based on these experiences and results, we have to realize that nonsurgical treatment of CWD is no contradiction but a helpful complement to treat congenital and acquired CWDs and may be applied for the majority of patients suffering from a CWD.
Keywords: pectus carinatum; pectus excavatum; nonsurgical treatment; orthotic brace; vacuum bell